2021
DOI: 10.3390/molecules26072086
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress, Chronic Ethanol Exposure, or the Combination, Alter Cannabinoid System Components in Reward and Limbic Regions of the Mouse Brain

Abstract: The cannabinoid system is independently affected by stress and chronic ethanol exposure. However, the extent to which co-occurrence of traumatic stress and chronic ethanol exposure modulates the cannabinoid system remains unclear. We examined levels of cannabinoid system components, anandamide, 2-arachidonoylglycerol, fatty acid amide hydrolase, and monoacylglycerol lipase after mouse single-prolonged stress (mSPS) or non-mSPS (Control) exposure, with chronic intermittent ethanol (CIE) vapor or without CIE vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…During adolescence, many brain areas are known to undergo functional and structural reorganization. Among the primary structures involved in stress, emotional regulation, motivation and reward, are the mPFC and the amygdala, which are vulnerable to the effects of chronic stress and alcohol exposure [45]. The ECS is widely expressed in both brain regions [46], and this system is also undergoing dynamic changes during adolescence [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence, many brain areas are known to undergo functional and structural reorganization. Among the primary structures involved in stress, emotional regulation, motivation and reward, are the mPFC and the amygdala, which are vulnerable to the effects of chronic stress and alcohol exposure [45]. The ECS is widely expressed in both brain regions [46], and this system is also undergoing dynamic changes during adolescence [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…These substances in particular warrant mention as both acute and chronic use can alter eCB functioning. For example, AEA levels in the corticolimbic brain regions (i.e., amygdala and frontal cortex) increase after chronic alcohol (Piggott et al, 2021), nicotine (González et al, 2002), and cannabis exposure in rodents (Di Marzo et al, 2002). While we found a significant difference between genotype groups in lifetime cannabis use, eliminating those who used the most (>100 uses) from our analyses did not change our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study demonstrated the involvement of CB1rs of the cerebellum in PTSD-like behaviors, showing significant sex differences that could explain, at least in part, the increased susceptibility of females to stress, anxiety, and PTSD [202]. However, in the mild single prolonged stress animal model of PTSD, the quantification of cannabinoid components (AEA, 2-AG, FAAH and MAGL) showed no differences between the model-exposed and control animals in different brain regions involved in mood and emotional processing [203].…”
Section: Animal Studiesmentioning
confidence: 94%